The effect of zinc supplementation on polymorphonuclear leukocyte functions of elder hypertensive patients and healthy young volunteers - (:unkn) unknown (My University, 2009)
Çinko desteği yaşlı hipertansiyonlu hastaların ve sağlıklı gençlerin polimorf nüveli lökosit (PNL fonksiyonlarını ( fagositoz ve hücre içi öldürme aktivitesi) stimüle edebilir. Bu çalışmanın amacı çinko desteğinin 13 yaşlı hipertansiyonlu hasta ile 10 sağlıklı gencin PNL fonksiyonları üzerine olan etkilerin in vitro koşullarda araştırmaktır. PNL’ler EDTA’lı venöz kandan Ficoll-Gradient santrifüj yöntemi ile ayrılmıştır. Fagositoz ve hücre içi öldürme aktivitesi tayininde Alexander ve arkadaşlarının yöntem modifiye edilerek kullanılmıştır. Yaşlı hipertansiyonlu hasta ve sağlıklı kişilere 30 gün boyunca 22mg/gün/oral olarak çinko desteği verilmiştir. Serum çinko düzeyleri atomik absorpsiyon spektrofotometresi ile belirlenmiştir. Çinko desteği öncesi yaşlı hipertansiyonlu hastaların serum çinko düzeyleri ve PNL’in hücre içi öldürme aktivitesi sağlıklı gençlere göre anlamlı olarak düşük bulunmuştur (p<0.001, p=0.001 sırasıyla). Çinko desteği sonrası yaşlı hipertansiyonlu hastaların PNL’lerin fagositik aktivitesi ve hücre içi öldürme aktivitesi sağlıklı gençlere göre anlamlı olarak düşük bulunmuştur (p<0.001, p<0.05 sırasıyla). Ancak çinko desteği sonrası yaşlı hipertansiyonlu hastaların serum çinko düzeyi destek öncesine göre artmıştır. Çinko desteği sonrası sağlıklı gençlerin serum çinko düzeyleri ile PNL’lerin fagositik aktivitesi anlamlı olarak artmıştır (p<0.05). Sonuç olarak, çinko desteği sonrası yaşl hipertansiyonlu hasta ve sağlıklı gençlerin serum çinko düzeyleri artmıştır. Doğru dozda yapılan çinko desteği yaşlı hasta ve sağlıklı gençlerin PNL’lerinin her 2 fonksiyonunu anlamlı olarak artırabilir .

Zinc supplementation can stimulate polymorphonuclear leukocyte (PMN) functions (phagocytosis and intracellular killing activity) in older hypertensive patients and healthy young volunteers. The aim of this study is to investigate the effect of zinc supplementation on polymorphonuclear leukocyte (PMN) functions (phagocytosis and intracellular killing activity) in vitro in 13 older hypertensive patients and compare these functions with those of 10 healthy young volunteers. PMNs were isolated by ficoll-hypaque gradient centrifugation method from venous blood with EDTA (0.1g/ml).Phagocytosis and intracellular killing activity were assayed by modifying Alexander’s method. The subjects were given zinc supplementation 22mg/daily/30 days. Serum zinc levels were measured by flame atomic absorption spectrometer. The serum zinc levels and the PMN’s intracellular killing activities of older hypertensive patients before zinc supplementation were significantly low when compared with that of healthy young volunteers (p<0.001, p=0.001 respectively). After zinc supplementation the PMN’s phagocytic and intracellular killing activities of older hypertensive patients were significantly lower than those of healthy young volunteers (p<0.001, p<0.05 respectively). However the serum zinc level of the elderly increased after zinc supplementation when compared with that before supplementation . The serum zinc levels and PMN’s phagocytic activity of healthy young volunteers significantly increased after zinc supplementation (p<0.05). Consequently, the serum zinc levels of the older hypertensive patients and young volunteers increased after zinc supplementation. Adequate zinc supplementation may improve PMN functions both in older hypertensive patients and healthy young volunteers.
Çinko desteğinin yaşlı hipertansiyonlu hasta ve sağlıklı gençlerin polimorf nüveli lökosit fonksiyonları üzerine etkisi
Keywords: Farmakoloji ve Eczacılık